Differences of Anxiety Levels between Students of Natural Sciences and Social Studies Major Based on School Environmental Factors in Senior High Schools with Rintisan Sekolah Bertaraf Internasional Scheme - Arviana Adamantina Putri; Leonardo Lubis; Tatang Muchtar Sutaryan (Althea Medical Journal, 2014)
Background: Senior High Schools with Rintisan Sekolah Bertaraf Internasional (RSBI) scheme are senior high schools that pilot international standards in learning methods and high curriculum targets. This factor may lead to a rise of anxiety amongst students, both for students in Natural Sciences major and Social Studies major. There are three factors which cause anxiety in the school environment, namely: dissatisfaction towards the curriculum, the teacher, and the school management.Methods: This study used retrospective cohort design. Subjects were selected using the convenience sampling method. Natural Sciences students (n=32) and Social Studies students (n=14) had their anxiety level measured using the Taylor Manifest Anxiety Scale. The dissatisfaction towards the school environment factors was assessed using a school evaluation questionnaire.Results: The anxiety measurement showed that students in both Natural Sciences and Social Studies major experienced severe anxiety (Natural Sciences vs. Social Studies: 75% vs. 86%). The study results based on the school evaluation questionnaire showed dissatisfactions towards the three school environmental factors (curriculum factor, Natural Sciences vs. Social Studies: 59% vs. 64%; teacher factor, Natural Sciences vs. Social Studies: 3% vs. 43%; school management factor, Natural Sciences vs. Social Studies: 3% vs. 14%). The chi-square test results showed that the difference in the anxiety levels between the students of Natural Sciences and Social Studies majors was insignificant (p>0.05).Conclusions: Students of Natural Sciences and Social Studies majors of senior high schools with RSBI scheme experienced severe anxiety. However, there is no strong evidence that the school environment causes this severe anxiety. Keywords: Anxiety Level, Natural Sciences, Senior High School with RSBI Scheme, School Environment Factors, Social Studies Perbedaan Tingkat Kecemasan antara Siswa Kelas Ilmu Pengetahuan Alam dan Siswa Kelas Sosial Berdasarkan Faktor Lingkungan Sekolah di Sekolah Menengah Atas Rintisan Sekolah Bertaraf InternasionalLatar Belakang: Sekolah Menengah Atas Rintisan Sekolah Bertaraf Internasional (SMA RSBI) adalah sekolah menengah atas yang menggunakan standar internasional dalam metode pembelajaran dan kurikulum.  Faktor ini dapat menyebabkan kenaikan kecemasan di kalangan siswa, baik bagi siswa kelas Ilmu Pengetahuan Alam dan siswa kelas Ilmu Sosial. Ada tiga faktor yang menyebabkan kecemasan di lingkungan sekolah, yaitu: ketidakpuasan terhadap kurikulum, guru, dan manajemen sekolah.Metode: Penelitian ini menggunakan desain kohort retrospektif. Subjek dipilih dengan menggunakan metode convenience sampling. Tingkat kecemasan siswa kelas Ilmu Pengetahuan Alam (n = 32) dan siswa kelas Ilmu Sosial (n = 14) diukur dengan menggunakan Skala Kecemasan Taylor Manifest. Ketidakpuasan terhadap faktor lingkungan sekolah dinilai menggunakan kuesioner evaluasi sekolah.Hasil: Pengukuran kecemasan menunjukkan bahwa siswa di kelas Ilmu Pengetahuan Alam dan Ilmu Sosial sama sama pernah mengalami kecemasan yang berat (Ilmu Pengetahuan Alam vs Studi Sosial: 75% vs 86%). Hasil penelitian berdasarkan kuesioner evaluasi sekolah menunjukkan ketidakpuasan terhadap tiga faktor lingkungan sekolah (faktor kurikulum, Ilmu Pengetahuan Alam vs Studi Sosial: 59% vs 64%; faktor guru, Ilmu Pengetahuan Alam vs Studi Sosial: 3% vs 43 faktor manajemen sekolah, Ilmu Pengetahuan Alam vs Ilmu Sosial;%: 3% vs 14%). Hasil uji chi-square menunjukkan bahwa perbedaan tingkat kecemasan antara siswa kelas Ilmu Pengetahuan Alam dan siswa kelas Ilmu Sosial jurusan tidak signifikan (p> 0,05).Simpulan: Siswa kelas Ilmu Pengetahuan Alam dan kelas Ilmu Sosial di SMA RSBI mengalami kecemasan yang berat. Namun, tidak ada bukti kuat yang menunjukkan bahwa lingkungan sekolah sebagai penyebab kecemasan yang berat ini.Kata kunci: Tingkat Kecemasan, Ilmu Pengetahuan Alam, SMA RSBI, Faktor Lingkungan Sekolah, Ilmu Sosial DOI: 10.15850/amj.v1n2.348